Mitigasi risiko umkm bongko melalui pendekatan house of risk (studi kasus: UMKM bongko bo’ limah Arosbaya) - Siti Nuridayanti Rahman; Resti Prastika Destiarni (AGROINTEK, 2024)
The Bongko production process often experiences obstacles due to less competitive workforce, miscommunications between the owner and the production department, and seasonal changes. This research was conducted to identify the factors that contribute to risk occurrences and how to prioritize risk sources while analyzing risk management in Bongko Bo' Limah MSME (Micro, Small, and Medium EnteRp.rises). This research was conducted from September - December 2022 with the research object was Bongko Bo' Limah MSME. The analytical method used in this study is House of Risk (HOR) analysis. Based on the identification results in HOR phase 1 showed that there were 27 risk events and 30 risk agents then prioritized to become 11 risk agents for risk mitigation. Recommendations for risk mitigation which were conducted to resolve 11 priority risk agents are analyzed through HOR phase 2 to obtain 10 risk mitigations that have been selected from the highest to the lowest based on value Effectiveness to Difficulty of Ratio (ETDk). It is hoped that this mitigation can be considered so that it can be implemented in dealing with exsisting risks to reduce potential operational activity losses.